Microvolt T wave alternans in adults with congenital heart diseases characterized by right ventricle pathology or single ventricle physiology: a case control study - Cieplucha, Aleksandra (BioMed Central, 2013)
BACKGROUND: Among adults with congenital heart diseases (CHD) evaluation of sudden cardiac death (SCD) risk remains a great challenge. Although microvolt T-wave alternans has been incorporated into SCD risk stratification algorithm, its role in adults with CHD still requires investigation. We sought to determine the incidence of MTWA in this specific group and its coincidence with ventricular arrhythmia (VA) and other clinical findings presumably associated with SCD. METHODS: A case–control study was performed in which 102 patients with CHD characterized by right ventricle pathology or single ventricle physiology (TGA, UVH, Ebstein’s anomaly, ccTGA, Eisenmenger syndrome, DORV, CAT, unoperated ToF) were compared to 45 age- and sex-matched controls. All subjects underwent spectral MTWA test, ambulatory ecg monitoring, cardiopulmonary test, BNP assessment. After excluding technically inadequate traces, the remaining MTWA results were classified as positive(+), negative(−) and indeterminate(ind). Due to similar prognostic significance MTWA(+) and (ind) were combined into a common group labeled ‘abnormal’. RESULTS: Abnormal MTWA was present more often in the study group, compared to controls (39.2% vs 2.3%, p = 0.00001). Sustained ventricular tachycardia (sVT) was observed more often among subjects with abnormal MTWA compared to MTWA(−): 19.4% vs 3.6%, p = 0.026. The patients with abnormal MTWA had a lower blood saturation (p = 0.047), more often were males (p = 0.031), had higher NYHA class (p = 0.04), worse cardiopulmonary parameters: %PeakVO(2) (p = 0.034), %HRmax (p = 0.003). Factors proven to increase probability of abnormal MTWA on multivariate linear regression analysis were: sVT (OR = 20.7, p = 0.037) and male gender (OR = 15.9, p = 0.001); on univariate analysis: male gender (OR = 2.7, p = 0.021), presence of VA (OR = 2.6, p = 0.049), NYHA > I (OR = 2.06, p = 0.033), %HRmax (OR = 0.94, p = 0.005), %PeakVO(2) (OR = 0.97, p = 0.042), VE/VCO(2)slope (OR = 1.05, p = 0.037). CONCLUSIONS: Abnormal MTWA occurs significantly more often in adults with the chosen forms of CHD than among healthy subjects. The probability of abnormal MTWA increases in patients with malignant VA, in males and among subjects with heart failure and cyanosis. MTWA might be of potential role in risk stratification for SCD in adults with CHD.